Upholding Faith and Religious Freedom: An Interpretation of the Qur’ānic Story of Young Cave Dwellers as a Religious Minority - Muh. Tasrif (Journal of Islamic Thought and Civilization, 2024)
The study of religious freedom for minorities has various aspects, such as legal, human rights, sociological, cultural, and religious aspects. Unfortunately, efforts to find solutions to protect religious freedom for minority groups have not made adequate use of the religious perspective, particularly Islamic. This research paper aims to fill the gap by analyzing and interpreting the active efforts of young cave dwellers described in the Qur’ān as a minority group. For this purpose, it used the qualitative descriptive approach based on the thematic interpretation of the Qur’ān. The study covered the story of young cave dwellers as narrated in the Qur’ān in al-Kahf 18:9-26. The story was analyzed in terms of its narrative context, storyline, similarities with other similar stories, and other crucial aspects. It was found that young cave dwellers actively fought for religious freedom by combining firmness in faith and positive adaptation in interacting with the society. The story  teaches us that religious freedom depends not only on the willingness of the majority group and the state but also on the proactive efforts of the minority group in behaving and acting on the diversity of religious views that surround them. For this reason, this paper contributes to provide conceptual solutions to the struggle of minority groups to fight for religious freedom amid religious diversity and views of life.